THE UNTOLD STORY OF HAVING A FAMILY MEMBER AS TERROR CONVICT: STUDY OF FAMILY HARDINESS & FAMILY PERSPECTIVE - Husna, Sabiqotul; Hidayat, Muslim (Jurnal Psikologi, 2023)
Families with members charged for terrorism face immense challenges. This study aims to understand family hardiness and family perspective of families who have family members as terrorists convict. Using a phenomenological approach, we explore family perspectives and family hardiness in three informants (father,mother, older sister of a terror convict). The results of this study reveal that family develops family hardiness through the stages of shock and early adaptation, surrender and believe in God during the hard times, confidence in dealing with difficult circumstances, identifying challenges and formulating constructive attitudes, and working together as a unit to control difficult situations. We also found how one family and its internal communication can possibly become the fuel to form a positive perspective, and to strengthen the belief to move forward. These results imply family hardiness is formed as a whole by the process of how a family accepts the effects of difficult situations and works together as a unit to overcome it. We call for more attention to strengthening support for families, at both social and policy levels, because these actions and initiatives can help families with difficult situations, e.g. a family who has a member as a terrorist convict to cope and adapt successfully, preventing them from experiencing severe psychological burdens and depression as they possibly received stigma and social exclusion.